STUDI KASUS BELAJAR ILMU PENGETAHUAN SOSIAL BAGI ANAK PENYANDANG MASALAH SOSIAL - Inayatullah Wijayanti; Sudjarwo Sudjarwo; Pargito Pagito (Jurnal Studi Sosial / Journal of Social Studies, 2014)
This study aims to determine how learning social studies conducted in schools whose students bear the social problems. This type of research is qualitative ethnographic approach. Based on the results obtained learning Social Studies run at schools with social problems in their students, it was not optimal. Lack of adequate facilities and infrastructure becomes a major factor. Social learning takes place only dependent on artificial student worksheet publisher. The specificity of the implemented learning social studies in schools whose students have social problems, is in the process of learning. The dominance of teachers is very high, and many students do not show creations. Description of the students and teachers in teaching social studies conducted in schools that have students bear the social problems. It turned out not to touch the Social Studies material aspects of the formation of national values. Learning instruments such as flag ceremonies, extracurricular activities, were never implemented. This happens because the institution does not provide space and time for the learning process is underway.Penelitian ini bertujuan untuk mengetahui bagaimana pembelajaran IPS dilaksanakan pada sekolah yang siswanya menyandang permasalahan sosial. Jenis penelitian yang digunakan yaitu kualitatif dengan menggunakan pendekatan studi kasus. Hasil penelitian diperoleh pembelajaran IPS dijalankan pada sekolah yang memiliki persoalan sosial pada siswanya, ternyata tidak maksimal. Kendala keterbatasan sarana dan prasarana menjadi faktor utama. Pembelajaran IPS berlangsung hanya tergantung kepada LKS buatan penerbit. Gambaran siswa dan guru dalam pembelajaran IPS yang dilaksanakan pada sekolah yang memiliki siswa menyandang masalah sosial. Ternyata materi IPS tidak menyentuh aspek pembentukan nilai-nilai kebangsaan. Instrumen pembelajaran seperti upacara bendera tidak pernah dilaksanakan. Hal ini terjadi karena lembaga pendidikan tidak menyediakan ruang dan waktu agar proses pembelajaran ini berlangsung.Kata kunci: anak penyandang, pembelajaran ips, masalah sosial